Cross-taxon relationships in Mediterranean urban ecosystem: A case study from the city of Trieste. (June 2021) - Zara, Laura; Tordoni, Enrico; Castro-Delgado, Silvia; Colla, Andrea; Maccherini, Simona; Marignani, Michela; Panepinto, Francesco; Trittoni, Michele; Bacaro, Giovanni
Highlights: Urban areas can support high level of vascular plant, ants and carabids. Cross-taxon congruence in urban ecosystem is a valid method for biodiversity assessment. Composition of vascular plants resulted a good surrogate of ant and carabid communities. Conservation measures are urged in urban areas to sustain biodiversity. Abstract: Urbanization directly and indirectly impacts biodiversity to the extent that it is considered one of the main causes of biotic homogenization and extinction. However, urban green areas can act as reservoir of biodiversity, and knowledge regarding species distribution in such contexts is crucial to define appropriate conservation and management strategies. Since inventories of species are generally time-consuming and costly, a commonly used approach consists in the use of surrogate species. However, studies investigating the effectiveness of surrogate species in urban environments still seem to be under-represented. In this research, we investigated the biodiversity of ants, plants, and carabid beetles in six different green areas within the urban area of the city of Trieste. The role of vascular plants as a potential surrogate for the diversity of ants and carabid beetles has been tested, investigating the influence of the environmental variables (dead wood, litter, anthropic disturbance, bare soil, bedrocks and rocks) on these relationships. Patterns of species richness and complementarity were compared among the sampled sites and their correlations were tested with Mantel tests and Co-Correspondence Analysis (Co-CA). Results pointed out that even disturbed and isolated sites within the urbanised matrix can sustain a high diversity of species of ants, carabids and plants, while in the semi-natural sites intermediate diversity levels were found. Plants were found to correlate directly with the diversity of ants; on the contrary, carabid species composition resulted only indirectly influenced by vascular plants, confirming the key role of abiotic variables in determining carabid diversity. Co-CA showed a clear distinction between forested and semi-natural environments and more open and disturbed environments. Furthermore, the Co-CA highlighted that the considered environmental variables (particularly dead wood, anthropic disturbance, rocks and litter) can significantly influence the distribution of analyzed taxa. Our results highlight the important role of urban green areas within the urban matrix as source of biodiversity and, furthermore, once more, support the role of vascular plants as meaningful surrogate for the diversity of ants and carabids.